PENGARUH KONSENTRASI PELARUT ETANOL DAN SUHU MASERASI TERHADAP RENDEMEN DAN KADAR KLOROFIL PRODUK ENKAPSULASI EKSTRAK SELADA LAUT (Ulva lactuca L) - Desi Trisna Dewi, Ni Nyoman; Wrasiati, Luh Putu; Ganda Putra, Gusti Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 3 (2016): September)
This research were aimed to 1) investigate the effect of ethanol concentration and temperature of maceration to rendement and chlorophyll content of sea lettuce extract powder, 2) investigate how the effect of  ethanol concentration and temperature of maceration  to  rendement and chlorophyll content of  sea lettuce  extract powder.  This experiment used randomized block design with 2 factors. The first factor was the ethanol concentration consists of 3 levels namely 70%, 80% and 90%. The second factor temperature of maceration consists of 4 levels namely 30 ± 2 o C, 45± 2 o C, 60 ± 2 o C and 75 ± 2 o C.  Variables observed were  rendement,  chlorophyll  a content,  chlorophyll  b  content    and total  chlorophyll content.  The result showed that ethanol concentration and  temperature of maceration  had high significantly effect on  chlorophyll  a content, while  did not affect on rendement. Interaction between ethanol concentration and temperature of maceration had high significantly effect on   chlorophyll  b  content  and  total chlorophyll content. Ethanol concentration 90% with temperature of maceration 45 ± 2 o C had the highest characteristic of sea lettuce extract powder at 27,08 % rendement, 97,07 ppm chlorophyll a content, 246,53 ppm chlorophyll b content and 306,28 ppm total chlorophyll content Keywords :  encapsulation, sea lettuce, ethanol concentration, temperature of maceration,  Ulva lactuca L
Keywords: 107,